(untitled) (Revista Electrónica Diálogos Educativos. REDE, 2017)
Given the difficulties in the completion of studies in the process of Higher Education, theoretical and practical studies developed in the area are surprisingly scarce.Â Historically, there has been a limited number of students that hand in their degree thesis after completing their credits at the School of Languages and Linguistics at the University of Guayaquil. Consequently, the problem faced in this paper is the insufficiencies in the completion of studies in relation to the management of the studentsâ€™ training. Thus, the objective is to improve the process of completion of studies for obtaining the university degree, through the implementation of a praxiological proposal of academic training and formative research integration management. The authorâ€™s systematization experiences invigorated the methodology used. Modeling the curricular management of academic training and formative research integration was revealed as the main proposal and solution to the problem diagnosed. As main results obtained, the students were able to solve educative problems diagnosed, while they drew up the first draft of their theses. In this way, this process was qualitatively and quantitatively improved. The proposal may be generalizable to any process of completion of studies involving degree thesis.